Findings of the ETLA survey on Finnish biotechnology firms - Raine Hermans; Terttu Luukkonen (The Research Institute of the Finnish Economy (ETLA), 2002)
This paper presents the first results of ETLA and Etlatieto Ltd Study of Finnish biotechnology firms. The majority of Finnish biotechnology firms are quite young and still in the early stages of gainful economic activities. Their turnover, profits and exports are, for the younger firms in particular, still low, profits even negative, while their growth expectations are high. The high R&D intensity of especially younger firms indicates that their products are still largely in the development phase and that few of their products are yet in the market. The commercialisation process is long, and only a few of the innovations eventually turn out to be exploitable. This increases the risk assessed and the rate of returns required by the investors. Private and public venture capitalists are most interested in the young companies with relatively high risk and high growth prospects. The oldest firms are more often subsidiaries. This may reflect the fact that foreign companies are willing to take over a Finnish company when its growth prospects are close to being realised. Furthermore, large proportion of the companies have obtained some public funding for the research which led to the foundation of the company or which took place in some other stages of the life cycle of the company. Research spin-off companies in general have more hindrances than other start-up firms, and would benefit from more systematic training in relevant business skills, such as how to make a business plan, how to deal with patenting, and how to obtain funding from venture capital investors.
Keywords: 330; Biotechnology firms; corporate finance; public funding of private R&D; R&D collaboration; Biotechnische Industrie; Unternehmensfinanzierung; Forschungssubvention; Forschungsfinanzierung; Public-Private Partnership; Finnland